«INFORMATIKA HÁM XABAR TEXNOLOGIYALARI» PÁNINEN ELEKTRON OQIW RESURSLARIN JARATIWDIŃ DIDAKTIKALIQ ÁHMIYETI - Allambergenova, M.X. (SCIENCE and SOCIETY, 2022)
This article talks about the creation of modern electronic educational literature and its didactic importance today.